Beginning Android programming with Android Studio - DiMarzio, J. F. (Wrox, A Wiley Brand, 2017)
"As the fastest-growing mobile platform today, the Android OS is a powerful and flexible platform for mobile devices and the new Android 5 release boasts significant new features and enhancements for both smartphone and tablet applications. This full-color resource takes a hands-on approach to teaching you how to create Android applications for the latest OS and the newest devices, including both smartphones and tablets." --Publisher annotation